CONSTRAINTS MILITATING AGAINST GOAT PRODUCTION IN ADAMAWA STATE - Yahya, M. M.; Midau, Alex (FUDMA JOURNAL OF SCIENCES, 2023)
In the tropics, small ruminants have low productivity partly due to slow growth rate which had been attributed to disease, poor nutrition, managerial factors and non-genetic factors such as age and parity of dam, sex and type of birth. The study was carried out to investigate the constraints of goats in Adamawa state. The design of the experiment was based on supplements offered. The result obtained in the study showed that: gestation length was short in groups receiving maize bran and cotton seed cake but longer in the control group and significant differences (P
Keywords: Birth weight; Gestation length; Red Sokoto goat; supplementation; twinning rate